Organic farming to achieve resilience and better food quality - Babalad, H B (Indian Farming, 2021)
As food security is not only a component of increased productivity, it also encompasses other issues of polices, trade, prices and environmental and resource use optimization. Organic farming as we see today is not the age-old traditional farming, it is a science based ecological intensification of cropping system with efficient management of on-farm resources, to achieve greater resilience in soil health and with comparable productivity of high quality food. Interdisciplinary research is needed in order to fully understand the likelihood of grower adoption and to support management recommendations that are deliberately tailored to unique agroecosystem contexts. With adequate policy support, organic agriculture can play a greater role in furthering the cause of food security and nutritional security in the country.